KONSEP PEMBAGIAN HARTA BERSAMA BERDASARKAN KONTRIBUSI DALAM PERKAWINAN - Muhamad Beni Kurniawan (AHKAM : Jurnal Ilmu Syariah, 2017)
This article describes marital property issues. How to devides marital property that can give justice to the parties. Becaused of that, this article provides a concept that can give justice to the parties ie marital property’s dstribution based on contributions in marriage. This concept is regarded more fair than the concept that provided by KHI. This study also gives religious court’s judges opinion about the concept of marital property’s distribution based on contributions in marriage. This article concludes that the conceptof marital property’s distribution based on contributions in marriage is thed istribution of marital property by assessment the contribution of the parties.In marital properties cases, if one party gives more contribution than the others, The judge can do contra legem. So that in casuistic, The distribution must not be 50% maybe the widower get 25% and the widow get 75% depend on their contributions. DOI: 10.15408/ajis.v17i2.4741